5‐(Piperidin‐4‐yl)‐3‐Hydroxypyrazole: A Novel Scaffold for Probing the Orthosteric γ‐Aminobutyric Acid Type A Receptor Binding Site. Issue 11 (26th August 2014) - Krall, Jacob; Kongstad, Kenneth T.; Nielsen, Birgitte; Sørensen, Troels E.; Balle, Thomas; Jensen, Anders A.; Frølund, Bente
Abstract A series of bioisosteric N1‐ and N2‐substituted 5‐(piperidin‐4‐yl)‐3‐hydroxypyrazole analogues of the partial GABAAR agonists 4‐PIOL and 4‐PHP have been designed, synthesized, and characterized pharmacologically. The unsubstituted 3‐hydroxypyrazole analogue of 4‐PIOL (2 a; IC50∼300 μM) is a weak antagonist at the α1β2γ2 GABAAR, whereas substituting the N1‐ or N2‐position with alkyl or aryl substituents resulted in antagonists with binding affinities in the high nanomolar to low micromolar range at native rat GABAARs. Docking studies using a α1β2γ2 GABAAR homology model along with the obtained SAR indicate that the N1‐substituted analogues of 4‐PIOL and 4‐PHP, 2 a–k, and previously reported 3‐substituted 4‐PHP analogues share a common binding mode to the orthosteric binding site in the receptor. Interestingly, the core scaffold of the N2‐substituted analogues of 4‐PIOL and 4‐PHP, 3 b–k, are suggested to flip 180° thereby adapting to the binding pocket and addressing a cavity situated above the core scaffold.